2013
DOI: 10.5194/hess-17-3937-2013
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and temperature estimation for a data sparse region

Abstract: Abstract. Humanitarian and development agencies face difficult decisions about where and how to prioritise climate risk reduction measures. These tasks are especially challenging in regions with few meteorological stations, complex topography and extreme weather events. In this study, we blend surface meteorological observations, remotely sensed (TRMM and NDVI) data, physiographic indices, and regression techniques to produce gridded maps of annual mean precipitation and temperature, as well as parameters for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…• Several diagnostics were derived noting that, because there are only five years of simulations, extreme rainfall can not be assessed. Instead, we have characterized how well WRF and SDSM simulate the following widely used indices (Haylock et al 2006;Wilby and Yu 2013;Nicholls and Murray 1999):…”
Section: Analytical Methods and Diagnostics Of Model Skillmentioning
confidence: 99%
“…• Several diagnostics were derived noting that, because there are only five years of simulations, extreme rainfall can not be assessed. Instead, we have characterized how well WRF and SDSM simulate the following widely used indices (Haylock et al 2006;Wilby and Yu 2013;Nicholls and Murray 1999):…”
Section: Analytical Methods and Diagnostics Of Model Skillmentioning
confidence: 99%
“…The IA (Willmott, 1981) is another widely used indicator of goodness of fit between observed and model output. IA (Eq.…”
Section: Comparing Ground Data With Satellite Observational Reanalysmentioning
confidence: 99%
“…In order to understand the impacts of future climate at the regional and local scale, ground station data with high spatial and temporal resolution are crucial. Regions with poor ground observations are highly vulnerable to climate threats (Wilby and Yu, 2013), which holds particularly for developing countries. In Africa, high-quality climate data from meteorological field stations are scarce (Dinku et al, 2013) and inconsistencies exist between other data products, largely due to a limited number of ground stations, merging and interpolation methods (Huffman et al, 2009;Nikulin et al, 2012;Sylla et al, 2013), limited time resolution, and limited documentation quality.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, studies in remote and data sparse areas, where most of the agricultural activities are happening, are limited. A study 22 concluded that regions with poor climate information are highly vulnerable to climate change and variability, which holds for East Africa. Identifying areas with a changing in climate (e.g., rainfall and temperature) requires spatial information with higher resolution, which could help better management of the impacts.…”
Section: Introductionmentioning
confidence: 99%